2021
DOI: 10.3390/ijms22168586
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic Acid Enhances Doxorubicin-Mediated Cytotoxic Effect in Osteosarcoma Cells

Abstract: Despite the recurring outbreak of resistance mechanisms and adverse reactions, doxorubicin (Doxo) still remains the standard-of-care for several cancers, including osteosarcoma (OS). As an appealing source of phytochemical compounds, naturally occurring molecules have extensively been reported to overcome Doxo limitations in preclinical models. Unlike other dietary polyphenols, only few studies recognize chlorogenic acid (CGA) as a potential partner in combination therapy, while, conversely, its anticancer evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 65 publications
2
13
0
Order By: Relevance
“…Furthermore, flow cytometry analysis reported that the dose-dependent manners of ononin dramatically enhanced the apoptotic rate in human osteosarcoma cells and MG-63-xenograft mice. This study was consistent with an earlier report that chlorogenic acid, a polyphenol, induced significantly apoptosis and cell death in MG-63 and U2OS cells [28]. In this present study, we compared the effectiveness of DOX on osteosarcoma cells with that of ononin, as a positive control.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, flow cytometry analysis reported that the dose-dependent manners of ononin dramatically enhanced the apoptotic rate in human osteosarcoma cells and MG-63-xenograft mice. This study was consistent with an earlier report that chlorogenic acid, a polyphenol, induced significantly apoptosis and cell death in MG-63 and U2OS cells [28]. In this present study, we compared the effectiveness of DOX on osteosarcoma cells with that of ononin, as a positive control.…”
Section: Discussionsupporting
confidence: 92%
“…This can be supported by the unique mechanisms observed for these compounds and the outcomes of several clinical trial investigations performed. For example, chlorogenic acid shows potential antitumor activity by inhibiting DNA methyltransferase 1 (DNMT1) expression [30][31][32][33]. Thus far, several cancer clinical trial investigations have been performed for this compound.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, chlorogenic acid inhibited hepatocellular carcinoma growth by down-regulating DNA methyltransferase 1 (DNMT1) that assists with DNA methylation, the most prevalent epigenetic modification [32]. Interestingly, chlorogenic acid was also found to show a synergistic effect with the anticancer drug, doxorubicin, against human U2OS and MG-63 osteosarcoma cells [33].…”
Section: Potential Antitumor Activity Of Aronia Berriesmentioning
confidence: 99%
“…"The antitumor and toxic effects of DXR contribute to the production of free radicals and to the occurrence of oxidative stress" [85]. "In this context, phytochemical compounds have been described as an alternative to mitigate the harmful effects caused by DXR since metabolites from natural products have shown to be promising in overcoming the limitations of DXR in pre-clinical models such as chemosensitizers, chemoresistance inhibitors, and protectors chemotherapeutics in different types of cancer" [86,87].…”
Section: Mechanisms Of Antitumor Actionmentioning
confidence: 99%